Investigation of Macular Structural and Microcirculatory Characteristics of Posterior Staphyloma in High Myopic Eyes by Swept Source Optical Coherence Tomography Angiography - Li, Haoru; Wang, Qingxin; Liu, Yucheng; Wang, Xin; He, Qing; Chen, Yanhui; Wei, Ruihua (Frontiers in Physiology, 2022)
Abstract Purpose: To investigate the characteristics of macular structures and microcirculation of posterior staphyloma (PS) and explored factors related to PS in eyes with high myopia. Methods: There were 114 eyes of 82 patients in this study. Using 1:1 matching of the axial length of myopic eyes, patients were divided into no PS (NPS) and PS groups. Comprehensive ophthalmic examinations were performed on all patients. Structural parameters were acquired using swept source optical coherence tomography (SS-OCT). OCT angiography (OCTA) was used to measure the microcirculation parameters. Generalized estimated equation and linear correlation analysis were used for the statistical analysis. Results: Patients with PS had a thinner retinal thickness (RT) and choroid thickness (CT) (all P < 0.05) in the measurement areas and a significantly lower subfoveal scleral thickness (SFST) (P < 0.001) than those without PS. Retinal deep vascular complex density (DVD) (all P < 0.05) and choroidal capillary perfusion area (CCPA) (all P < 0.001) were significantly lower in the measurement areas of the PS group than in those of the NPS group. There was no significant difference in the retinal superficial vascular density between the two groups. Generalized estimating equation indicated that SFST (B = 0.079, P = 0.001), parafoveal RT (B = -0.162, P = 0.041), foveal CT (B = 0.292, P = 0.013), parafoveal CT (B = -0.157, P = 0.023), foveal CCPA (B = 0.691, P = 0.003) and parafoveal CCPA (B = -0.026, P = 0.004) were significantly correlated with PS. Age (r = -0.323, P = 0.001), spherical equivalent refraction (SER) (r = 0.289, P = 0.004), subfoveal CT (r = 0.398, P < 0.001), foveal DVD (r = 0.346, P < 0.001), foveal CT (r = 0.429, P < 0.001), and foveal CCPA (r = 0.387, P < 0.001) were strongly correlated with SFST.